Motivation of EFL Vietnamese Students in Economics-related Majors - Minh Tuyet Thi Le; Trang Huynh Nguyen (Vietnam Journal of Education, 2023)
Motivation plays an essential part in learning, especially in second language acquisition (SLA). This paper investigates the learning motivation of Vietnamese economics-related majors studying English as a Foreign Language (EFL), utilizing Dornyei’s (2005) L2 motivational self-system as the theoretical framework. The subjects were 236 first-year and 99 second-year students. A mixed method research design with both quantitative and qualitative approaches was employed. The 6-point scale questionnaire was adapted from Dörnyei’s (2005, 2009), including 24 items to explore students’ Ideal L2 Self, the Ought-to L2 Self, the students’ attitudes and their effort in learning English. The quantitative data were analyzed with SPSS software for Mean, Standard Deviation, and correlations. The open-ended section and focus group interview probed further into the students’ motivation, influencing factors, as well as the student recommendations for stakeholders in order to enhance their motivation to learn English. The study proposes some implications for EFL instructors, curriculum developers, and administrators to promote students’ motivation in English learning.